KEGUNAAN SISTEM PENGOTOMATAN (OTOMASI) LABORATORIUM/ LAS (LABORATORY AUTOMATION SYSTEMS) - Prihatini . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
In most laboratory LAS (Laboratory Automation System) system recently have been used. though, not all of them used theautomation system and LIS.the LAS is used for the diagnosis of diseases, because it can decrease the error factors as weel as thelaboratoric examination. Regarding to decreasing problems, the expenses of patients who staying in the hospitals could be reduced aswell as their time to stay. the purpose of this article is to know comprehensively LAS and its services in the future in the hospitals' clinicallaboratory. Because before LAS was used the diagnosis time of diseases take a long time as compared to LAS.